Influencia de un sistema de videovigilancia en los procesos de comercialización en AGA Representación SAC sucursal Jaén - 2014 - Sánchez Lozano, Franz Joan (2015)
The following research named, "INFLUENCE OF VIDEO SURVEILLANCE SYSTEM IN THE PROCESS OF MARKETING BRANCH OF AGA REPRESENTACION SAC JAEN"; has as General Purpose to improve marketing processes of AGA Representations SAC branch Jaen allowing an efficient and timely control. Also specific objectives; Implement an IT security and control infrastructure based on a video surveillance system; Set security policies and control in marketing processes; Redesign marketing processes in control and security; Train staff in the use of information technologies for the sustainability of the project, for efficient control between different areas so that marketing processes are optimized. For the development of the proposed different methodologies were used. For information gathering techniques of observation, interviews were conducted, as well as documents reviewing and assessment; for the location of the points of installation of surveillance cameras critics and main access points to the company analyzed. Having regard to the need to improve marketing processes and reduced wastage by systematic theft in AGA Representations SAC, and thus achieve greater control of the Company with the implementation of a system of timely transmission of video surveillance in daily revenues to the entity; this project aims to improve and optimize the control of the company AGA Representation SAC Jaen branch through a system of monitoring and security through surveillance cameras.